Structure, expression and regulation of the cannabinoid receptor gene (CB1) in Huntington's disease transgenic mice - Elizabeth A. McCaw; Haibei Hu; Geraldine T. Gomez; Andrea L.O. Hebb; Michael E. Kelly; Eileen M. Denovan‐Wright (2004)
Loss of cannabinoid receptors (CB1) occurs prior to neurodegeneration in Huntington's disease (HD). The levels and distribution of CB1 RNA were equivalent in 3-week-old mice regardless of genotype demonstrating that the specific factors and appropriate chromatin structure that lead to the transcription of CB1 were present in the striatum of young R6/2 and R6/1 transgenic HD mice. The expression of the mutant HD transgene led progressively to decreased steady-state levels of CB1 mRNA in neurons of the lateral striatum, which was dependent on the size of the CAG repeat and relative expression of the gene encoding mutant huntingtin (HD). Although it is known that the coding region of CB1 is contained within a single exon in mice, rats and humans, the 5′-untranslated region of the mouse gene remained to be defined. CB1 mRNA is encoded by two exons separated by an 18.4-kb intron. Transcription of CB1 occurred at multiple sites within a GC-rich promoter region upstream of exon 1 encoding the 5′-UTR of CB1. There was no difference in the selection of specific transcription initiation sites associated with higher levels of CB1 expression in the striatum compared to the cortex or between the striata of wild-type and HD transgenic mice. The progressive decline in CB1 mRNA levels in R6 compared to wild-type mice was due to decreased transcription, which is consistent with the hypothesis that mutant huntingtin exerts its effects by altering transcription factor activity. The cell-specific conditions that allow for increased transcription of CB1 in the lateral striatum compared to other forebrain regions from all transcription start sites were affected by the expression of mutant huntingtin in a time-dependent manner.